Closed-loop controller design, stability analysis and hardware implementation for fractional neutron point kinetics model - Vishwesh A. Vyawahare; G. Datkhile; P. Kadam; G. Espinosa-Paredes (Nuclear Engineering and Technology, 2021)
The aim of this work is the analysis, design and hardware implementation of the fractional-order point kinetics (FNPK) model along with its closed-loop controller. The stability and closed-loop control of FNPK models are critical issues. The closed-loop stability of the controller-plant structure is established. Further, the designed PI/PD controllers are implemented in real-time on a DSP processor. The simulation and real-time hardware studies confirm that the designed PI/PD controllers result in a damped stable closed-loop response.